2020
DOI: 10.1002/jsfa.10648
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestibility of mountain‐grown irrigated perennial legume, grass and forb forages is influenced by elevated non‐fibrous carbohydrates and plant secondary compounds

Abstract: BACKGROUND Perennial legumes cultivated under irrigation in the Mountain West USA have non‐fibrous carbohydrate (NFC) concentrations exceeding 400 g kg−1, a level commonly found in concentrate‐based ruminant diets. Our objective was to determine the influence of NFC concentration and plant secondary compounds on in vitro rumen digestion of grass, legume and forb forages compared with digestion of their isolated neutral detergent fiber (NDF) fraction. Forages were composited from ungrazed paddocks of rotational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The elevated level of readily digested carbohydrates combined with the protection of soluble protein from digestion in the rumen appeared in this study to result in greater ADG for steers grazing BFT than either CMV or a high-quality grass. Cicer milkvetch has been found to contain a water-soluble arabinogalactan protein that prevents cellulolytic bacteria from adhering to cellulose [39,40], which likely reduced the maximum rate of in vitro fermentation of CMV relative to BFT in this and other studies [41].…”
Section: Forage Production and Qualitymentioning
confidence: 58%
“…The elevated level of readily digested carbohydrates combined with the protection of soluble protein from digestion in the rumen appeared in this study to result in greater ADG for steers grazing BFT than either CMV or a high-quality grass. Cicer milkvetch has been found to contain a water-soluble arabinogalactan protein that prevents cellulolytic bacteria from adhering to cellulose [39,40], which likely reduced the maximum rate of in vitro fermentation of CMV relative to BFT in this and other studies [41].…”
Section: Forage Production and Qualitymentioning
confidence: 58%
“…As sainfoin contains moderate to high percentage of CT, it may affect palatability and also reduce nutrient digestibility due to its binding ability effect (Scharenberg, Arrigo, Gutzwiller, Soliva, et al, 2007). Numerous in vitro studies also demonstrated that sainfoin had lower gas production, degradable DM and OM and VFA production (Copani et al, 2015;Grosse Brinkhaus et al, 2017;Wang et al, 2022) and also NDF digestibility (Zhang et al, 2021) compared to alfalfa and grass.…”
Section: Small Ruminants' Performancementioning
confidence: 99%
“…Forage is the primary source of feed for fulfilling the nutrient requirements of ruminants, including grasses, legumes, and herbs. In addition, this feed plays an essential role in providing dietary fiber, energy, protein, as well as essential vitamins and minerals (Zhang et al 2020). Several studies have shown that the quality of forages can be assessed using their nutritive value, particularly Crude Protein (CP), Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Acid Detergent Lignin (ADL), and Water-Soluble Carbohydrates (WSC) (Küchenmeister et al 2013;Brown et al 2017).…”
Section: Introductionmentioning
confidence: 99%